Decrease of HCV seroprevalence in Mexico: Results from the National Health and Nutrition Survey 2012 - Juan Pablo Gutiérrez; Héctor Sucilla-Pérez; Carlos J Conde-González; José Antonio Izazola; Martin Romero-Martínez; Mauricio Hernández-Ávila (Instituto Nacional de Salud Pública, 2016)
Objective. To estimate seroprevalence of hepatitis C virus (HCV) among 15-49 years old Mexicans living in households and to describe the profile of seroreactive individuals. Materials and methods. Cross-sectional study implemented in 2012 using a national probabilistic sample with behavioral data from face-to-face interviews at households and HCV antibodies screening using capillary blood from same individuals. Results. HCV seroprevalence in Mexico was estimated at 0.27% (IC95% 0.12-0.60), representing 161 000 persons. Seroprevalence was significantly higher among males (0.45% CI95% 0.01-0.89) than females (0.10% CI95% 0.00-0.22). Multivariate analysis suggests a higher possibility of HCV reactivity among men, increasing with age and higher among those sexually active, and lower for higher socioeconomic level. Conclusion. HCV seroprevalence in Mexico by 2012 seems significantly lower than the estimation from 2000 of 1.2% for the same age-group. Evidence of infection among individuals 15-19 years old suggests the need to strength pre- ventive actions, particularly in subjects with risky behaviors.